Sprinter: A didactic linter for structured programming - Alfredo, F. (2022)
Code linters are tools for detecting improper uses of programming constructs and violations of style issues. Despite that professional linters are available for numerous languages, they are not targeted to introductory programming, given their prescriptive nature that does not take into consideration a didactic viewpoint of learning programming fundamentals. We present Sprinter, a didactic code linter for structured programming supporting Java whose novelty aspects are twofold: (a) providing formative feedback on code with comprehensive explanatory messages (rather then prescriptive); (b) capability of detecting some control-flow issues to a deeper extent than professional linters. We review Sprinter features against popular tools, namely IntelliJ IDEA and Sonarlint.